Peak inequality : Britain's ticking time bomb - Dorling, Daniel (Policy Press, 2018)
Dorling brings together new material alongside a selection of his most recent writing on inequality from publications including the Daily Telegraph, the Guardian, New Statesman, Financial Times and the China People's Daily. He explores whether we have now reached 'peak inequality' and concludes by predicting what the future holds for Britain.